Synovial fibroblasts modulate endothelial activation in an acute injury-on-a-chip model - Hannah M. Zlotnick; Declan N. Goddard; Christopher J. Calo; Abhishek P. Dhand; Matthew D. Davidson; Aina Solsona-Pujol; Jonathan T. Makhoul; Hannah K. Weppner; Melissa Wong; Carla R. Scanzello; Laurel E. Hind; Jason A. Burdick (Proceedings of the National Academy of Sciences, 2026)
Most patients who sustain an acute joint injury develop degenerative joint disease or osteoarthritis (OA). Animal models have informed the design of OA therapeutics; however, no disease-modifying therapy has successfully translated to human patients. Thus, there is a strong motivation to develop humanized in vitro platforms to fill a critical gap in knowledge of disease progression postinjury. Here, we develop an acute injury-on-a-chip model of the synovium, a vascularized, joint-lining tissue that has been implicated in OA progression and as a key driver of joint disease. We apply this chip-based system to investigate the crosstalk between endothelial cells, lining an engineered vessel, and synovial fibroblasts, embedded within an extracellular matrix hydrogel. Our data indicate that synovial fibroblasts, rather than initiating disease, attempt to support and maintain vascular function in the presence of acute inflammation (i.e., interleukin-1β). Such knowledge may provide new targets for OA therapeutics, preventing the progression from joint injury to disease in patients.